Sistem Layanan Sirkulasi Pada Perpustakaan Umum Dinas Perpustakaan dan Kearsipan Kota Payakumbuh - Ishna Zulhaj; Malta Nelisa (Istinarah: Riset Keagamaan, Sosial dan Budaya, 2022)
This study aims to describe the existing circulation service system at the Public Library of the Payakumbuh City Library and Archives Service. What will be seen or examined in this study are what circulation services are available, what are the service procedures, and the constraints and efforts to deal with the obstacles encountered in the service. The research method used is a descriptive method by taking data directly to the field. Data collection techniques used observation and documentation that were carried out during an internship at the Public Library of the Payakumbuh City Library and Archives Service. The results obtained are that the circulation services available at the Public Library of the Payakumbuh City Library and Archives Service include membership services, borrowing, returning and imposing sanctions. Service procedures are still carried out manually and the obstacles faced lie in the users and the tools used by librarians to help with their work.